Hubungan Asupan Bahan Makanan Sumber Serat, Asupan Natrium, Asupan Lemak dan IMT dengan Tekanan Darah pada Pasien Hipertensi Rawat Jalan di Rumah Sakit Tugurejo Semarang - Nur Yunaida Fauziah; Sufiati Bintanah; Hapsari Sulistya Kusuma (Universitas Muhammadiyah Semarang, 2015)
High blood pressure disease shows enhanced from to year. High blood pressure at influence by behaviour factor that is food pattern unfavourable likes to consumption over source sodium, less to consumpt fibrous food likes fruit and vegetable, risk factor of the increasing of blood pressure besides fat factor and Body Mass Index (BMI). The increasing of blood pressure also influenced by genetic factor.fat consumtion and obesitas. The purpose of the research is to detect the correlation of fiber consumption, sodium intake, fat and BMI with blood pressure in hypertension patient in care at Hospital Tugurejo SemarangResearch kind uses method explanatory research at clinic nutrient area with a cross sectional approached. The size of population as much as 63 person and sample 55 person, was taken by purposive sampling. Data becollected by using direct interview methode in sufferer. Primary data that is gatherred to cover: food-stuff consumption that contain fiber by recall use food frequency and questionnaire. The normality of the data was tested by kolmogorov smirnov test. The correlation of variables, were analysed by correlation pearson product moment test if the distribution of data is normal and use spearman rank test if the data not normally distribution.There are no correlation between fiber, fat, sodium and BMI with blood pressure. Necessary done continuation research to detect factors that causes hypertension besides sodium intake, fat, fiber and BMI by using different technique and method and with mare many of sample